After Whom the Instruments Named - Hosain, Suman Nazmul (Cardiovascular Journal, 2014)
Innovation in surgery plays a very important role of easing the task of the surgeons. Some instruments used in cardiac surgery today were designed by legendary surgeons from the past. These useful articles bear the names of their inventors. There hasnt been much documentation on the development of cardiothoracic surgical instruments. The historian claims that first known surgical instruments were developed as early as 10,000 BC! Hippocrates had reportedly developed different surgical instruments made of copper, iron, bronze, and brass. Renowned Muslim surgeon of middle age Al-Zahrawi devised many surgical instruments. Some surgeons developed instruments based on their own anatomical size and others for new operations that required more delicate instrumentation to perform them. Cardiothoracic surgeons also have adopted instruments innovated, designed and used by colleagues belonging to other surgical specialty. This article would explore a few of these legendary innovators, illuminating the drive that led these legends to design the surgical instruments we continue to use in our surgical practices even today. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18366 Cardiovasc. j. 2014; 6(2): 184-188